Structural Equation Modeling applied to the analysis of staying in risk areas: Case study of the Beira city (Research, Society and Development, 2025)
Mozambique, and specifically the city of Beira, faces high vulnerability to floods and cyclones, exacerbated by its low coastal elevation and disorganized urban expansion into risk areas. This vulnerability is multidimensional. This study aimed to analyze the determining factors of the population's permanence in Beira's risk zones, despite the threat of recurrent disasters. A quantitative study was conducted, surveying 337 individuals in vulnerable neighborhoods. Structural Equation Modeling (SEM) was used to investigate the impact of economic, social/cultural, psychological, and structural factors on the intention to stay. SEM revealed that the main determinant of permanence is the social/cultural factor (β=0.978, p